COMMON GRAMMATICAL ERRORS MADE BY BEGINNER LEVEL STUDENTS (A STUDY OF LANGUAGE INTERFERENCE) - -, Maisarah (Educate, 2012)
ABSTRACT First language has a significant effect on the second language acquisition. Indonesian ESL learners, particularly those of beginner learners, often refer to Bahasa Indonesian (L1) when they produce English sentences or utterance. This kind of phenomenon in the study of second language acquisition is called the interference of first language into second language (negative interlingual transfer). The result of the study showed that the errors occurred are preposition errors, article errors, verb errors, noun errors, conjunction errors, adjective errors, word order errors, and time expression errors. Markedness, besides the fact that they were intermediate-level students, was the most obvious factor that contributes to the errors. This means when a certain grammar rule in L2 (English) is more complex, the students were inclined to make errors. Some different structures between English and Bahasa Indonesia might contribute to errors as well. When the respondents faced certain English grammar which was different from that of Bahasa Indonesia, they tended to use their knowledge of L1 to construct the sentences. As a result, their sentence production sometimes fell into errors. Keywords: L1 interference, markedness, First-year students